Kajian Historis tentang Islam di Spanyol dan Perkembangannya - Ariyanti Alwan; Ansar Tohe (Al-Kindi, 2026)
This study comprehensively examines the history of the arrival of Islam in Spain (Al-Andalus), as well as its development and decline over nearly eight centuries (711–1492 CE). Employing a historical-descriptive and analytical approach based on library research, the article explores the socio-political background of pre-Islamic Spain, the conquest led by Tariq ibn Ziyad and Musa ibn Nusayr, the political dynamics of Islamic rule—spanning the eras of the governors, the Umayyad Caliphate, the Almoravids, the Almohads, and the Nasrid dynasty—and the factors driving civilizational advancement and eventual decline. The findings indicate that the success of Islam in building a civilization in Spain was underpinned by social cohesion, intellectual vigor, and a policy of tolerance (*convivencia*) that facilitated cultural exchange among Muslims, Christians, and Jews. However, internal divisions, political conflicts, and the *Reconquista* movement were the primary factors leading to the collapse of Islamic rule. The legacy of Islamic civilization in Spain contributed significantly to the European Renaissance through the transfer of knowledge, philosophy, and technology. The study concludes that Islamic civilization in Spain was not merely a historical episode but a pivotal milestone that shaped modern European civilization.